Proposição de uma ferramenta que colabore na tomada de decisão em estudos de viabilidade de empreendimentos imobiliários com uso do BIM - Marinho, Renan Caminha (2020)
The launch of a new real estate development is surrounded by risks and uncertainties for developers. Thus, so that entrepreneurs can invest their resources in civil construction, it is necessary to carry out more reliable economic feasibility studies to support decision making. However, the economic evaluation of projects is often performed intuitively by business owners or decision makers, without considering the most appropriate techniques for feasibility analysis. Thus, in the face of this scenario, developers are always looking for ways to optimize their work and Building Information Modeling (BIM) has become an increasingly important differential due to its many features, such as simulations, 3D visualization and automatic budgeting. . However, the design process with BIM is still a largely manual process, depending on the designer's experience with the tools for the model to function properly. To circumvent this situation, there is the generative project, which seeks to automate and systematize solutions with BIM, through visual programming. Thus, the objective of this study is to develop a tool that collaborates in decision making in feasibility studies for real estate projects in civil construction, using BIM models aided by visual programming. For that, an artifact was elaborated, based on the application of Design Science Research, surveying the main parameters and aspects of projects involved in feasibility studies, through bibliographic surveys and interviews with specialists, to elaborate a model proposal, which it was later transformed into a visual programming code, capable of generating a greater number of feasibility study scenarios, following the urban limits related to the land, with different costs, in a shorter time, thus facilitating decision making. The artifact was tested with specialists, using real cases of projects already consolidated, to search for suggestions and improvements. With the complement of the code referring to the demands requested in the code evaluation, a new case was simulated, reaching similar results to the real ones found for the enterprise in question..